ANALISIS PERLAKUAN PANAS NORMALISING PADA PENGELASAN ARGON TERHADAP SIFAT MEKANIK HASIL LASAN BAJA KARBON RENDAH - Widodo, Basuki (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2009)
Welding is a fabric Welder i.e a fabrication process that applied to joint metal material by using temperature dissociation energy of diatomic. Up to this day, welding has been used widely on joining steel and engine constructions. The influence of thermal cycle on welding causes metallurgical changes i.e residual stress and changes of mechanical characteristics (hardness, strength tensile, reconnaissance of macro and micro structures) on the result of low carbon steel weldment. This research was done to obtain the proper treatment for normalizing weldment result on different current to mechanical character. The value of hardness and strength tensile is best obtained after normalizing process at temperature of 8600C is at the current of 140A with hardness mean value of 78,67 HRB ( weld), 73,89 HRB ( HAZ) and 70,11 HRB ( mains), while strength tensile is 45,835 Kgf/mm2.